2021
DOI: 10.3892/ijo.2021.5294
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of METTL6 mitigates cell progression, migration, invasion and adhesion in hepatocellular carcinoma by inhibiting cell adhesion molecules

Abstract: RNA modifications have attracted increasing interest in recent years because they have been frequently implicated in various human diseases, including cancer, highlighting the importance of dynamic post-transcriptional modifications. Methyltransferase-like 6 (METTL6) is a member of the RNA methyltransferase family that has been identified in many cancers; however, little is known about its specific role or mechanism of action. In the present study, we aimed to study the expression levels and functional role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
(66 reference statements)
0
22
0
1
Order By: Relevance
“…RNA modifications play a key role in regulating cell fate, an important regulator of HCC, in tumorigenesis and disease progression (Han et al, 2018;Pea et al, 2021;Braghini et al, 2022). The m6A, m7G, m5C, m1A, m3C, and ψ RNA modifications dynamically regulate the development of HCC, providing new strategies and possibilities for selecting possible therapeutic targets and investigating precisely directed intervention strategies for future HCC therapy (Tian et al, 2019;Bolatkan et al, 2022;Liu et al, 2022;Ren et al, 2022;Tong et al, 2022;Yu et al, 2022). As the most intensively studied RNA modification, m6A, and its regulators regulate the proliferation, migration, invasion, and EMT processes of HCC cells and are promising targets for HCC therapy (Zhou et al, 2019b;Liu et al, 2020a;Wang et al, 2020b;Zhang et al, 2020c;Qu et al, 2020;Wu et al, 2020;Zhu et al, 2020;Li et al, 2021e;Wei, 2021;Gu et al, 2022;Ren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RNA modifications play a key role in regulating cell fate, an important regulator of HCC, in tumorigenesis and disease progression (Han et al, 2018;Pea et al, 2021;Braghini et al, 2022). The m6A, m7G, m5C, m1A, m3C, and ψ RNA modifications dynamically regulate the development of HCC, providing new strategies and possibilities for selecting possible therapeutic targets and investigating precisely directed intervention strategies for future HCC therapy (Tian et al, 2019;Bolatkan et al, 2022;Liu et al, 2022;Ren et al, 2022;Tong et al, 2022;Yu et al, 2022). As the most intensively studied RNA modification, m6A, and its regulators regulate the proliferation, migration, invasion, and EMT processes of HCC cells and are promising targets for HCC therapy (Zhou et al, 2019b;Liu et al, 2020a;Wang et al, 2020b;Zhang et al, 2020c;Qu et al, 2020;Wu et al, 2020;Zhu et al, 2020;Li et al, 2021e;Wei, 2021;Gu et al, 2022;Ren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis of METTL6 in HCC revealed that METTL6 mRNA expression levels were significantly upregulated in HCC and were closely associated with poorer patient survival outcomes. In contrast, METTL6 downregulation inhibited HCC progression by suppressing cell adhesion molecules and could be a potential therapeutic target for HCC (Bolatkan et al, 2022). METTL6mediated m3C tRNA methylation regulates gene expression, cellular homeostasis, translation, and tumor cell growth (Ignatova et al, 2020;Bolatkan et al, 2022).…”
Section: Role Of N3-methylcytosine In Hepatocellular Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have assessed RNA methylation modifications in recent years, their mechanism of development in tumors is still not fully elucidated. 7 The Cancer Genome Atlas (TCGA) is a tumor genomics program that aims to use high-throughput genomic analysis techniques to better understand tumor characteristics and improve tumor prevention, diagnosis, and treatment. 8 , 9 Currently, TCGA contains information about sequencing results, transcriptome analysis, copy number variants, DNA methylation, and single nucleotide variants and covers 33 tumor types, thereby providing an advantage in pan-cancer research.…”
Section: Introductionmentioning
confidence: 99%